2001
DOI: 10.4141/p00-145
|View full text |Cite
|
Sign up to set email alerts
|

Three-component barley mixtures: Ratio effects in replacement series

Abstract: . 2001. Three-component barley mixtures: Ratio effects in replacement series. Can. J. Plant. Sci. 81: 651-656. Within a species, cultivar mixtures may offer yield and quality advantages if the cultivars have complementary abiotic and biotic stress tolerances. This study was conducted at Botha, Lacombe and Olds, Alberta, from 1992 to 1994 to determine the effect of relative seeding ratios on yield and other traits of 16 three-component barley (Hordeum vulgare L.) mixtures of Virden:Abee:Tukwa all grown at a sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
13
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 18 publications
3
13
0
Order By: Relevance
“…4). We found that b i values were sometimes higher than that of all their components (Mix3 and Mix4), whereas Juskiw et al (2001) by a comparable approach found b i values of mixtures to be intermediate relative to component values. In the review of 36 studies, Smithson and Lenné (1996) found the environmental regression coefficients of both mixtures and component varieties to be very variable between studies.…”
Section: Yield and Stability Analysismentioning
confidence: 72%
See 2 more Smart Citations
“…4). We found that b i values were sometimes higher than that of all their components (Mix3 and Mix4), whereas Juskiw et al (2001) by a comparable approach found b i values of mixtures to be intermediate relative to component values. In the review of 36 studies, Smithson and Lenné (1996) found the environmental regression coefficients of both mixtures and component varieties to be very variable between studies.…”
Section: Yield and Stability Analysismentioning
confidence: 72%
“…These stability concepts are frequently used to compare crop properties (for a review, see Piepho 1998), including comparisons of variety mixtures and their components (e.g. Smithson and Lenné 1996;Juskiw et al 2001;Cowger and Weisz 2008). Here, the overall yield variation, of mixtures was slightly higher than that of pure stand varieties, and since this measure encompasses both the response to environmental productivity and sensitivity to weeds and diseases, it seems more informative to consider these sources of variation separately.…”
Section: Yield and Stability Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…One of the solutions that may have potential for improving field pea competitive ability is genotypic mixtures. Genotypic mixtures have been proposed as a sustainable alternative to improve crop productivity (Wolfe 1985;Sarandon and Sarandon 1995;Jedel et al 1998) because they tend to allow the crop to adjust to varied biotic and abiotic stresses during the growing season (Wolfe 1985;Juskiw et al 2001). Several studies have investigated the potential use of genotypic mixtures, with some studies finding a small increase in grain yield when mixtures were compared with pure stands.…”
Section: Mots Clé Smentioning
confidence: 99%
“…The weaker cultivar diversity-productivity relationship may reflect the much narrower range of genotypic and phenotypic diversity found in a single plant group (cereals) compared with three crop groups (cereals, oilseeds and legumes). Juskiw et al (2001) also reported that barley cultivar mixtures had no yield advantage over growing a highly productive mono-cultivar crop. Nevertheless, Essah and Stoskopf (2002) found that mixtures of phenotypically different barley cultivars can produce yield advantages over mono-cultivar crops.…”
Section: Resultsmentioning
confidence: 99%